Structural and Functional Changes in the Coupling of Fascial Tissue, Skeletal Muscle, and Nerves During Aging - Zullo, Alberto; Fleckenstein, Johannes; Schleip, Robert; Hoppe, Kerstin; Wearing, Scott; Klingler, Werner (Frontiers in Physiology, 2020)
Aging is a one-way process associated with profound structural and functional changes in the organism. Indeed, the neuromuscular system undergoes a wide remodeling, which involves muscles, fascia, and the central and peripheral nervous systems. As a result, intrinsic features of tissues, as well as their functional and structural coupling, are affected and a decline in overall physical performance occurs. Evidence from the scientific literature demonstrates that senescence is associated with increased stiffness and reduced elasticity of fascia, as well as loss of skeletal muscle mass, strength, and regenerative potential. The interaction between muscular and fascial structures is also weakened. As for the nervous system, aging leads to motor cortex atrophy, reduced motor cortical excitability, and plasticity, thus leading to accumulation of denervated muscle fibers. As a result, the magnitude of force generated by the neuromuscular apparatus, its transmission along the myofascial chain, joint mobility, and movement coordination are impaired. In this review, we summarize the evidence about the deleterious effect of aging on skeletal muscle, fascial tissue, and the nervous system. In particular, we address the structural and functional changes occurring within and between these tissues and discuss the effect of inflammation in aging. From the clinical perspective, this article outlines promising approaches for analyzing the composition and the viscoelastic properties of skeletal muscle, such as ultrasonography and elastography, which could be applied for a better understanding of musculoskeletal modifications occurring with aging. Moreover, we describe the use of tissue manipulation techniques, such as massage, traction, mobilization as well as acupuncture, dry needling, and nerve block, to enhance fascial repair.